2009
DOI: 10.1128/jb.00749-09
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of theHelicobacter pyloriFlagellar Switch Proteins

Abstract: Helicobacter pylori uses flagellum-mediated chemotaxis to promote infection. Bacterial flagella change rotational direction by changing the state of the flagellar motor via a subcomplex referred to as the switch. Intriguingly, the H. pylori genome encodes four switch complex proteins, FliM, FliN, FliY, and FliG, instead of the more typical three of Escherichia coli or Bacillus subtilis. Our goal was to examine whether and how all four switch proteins participate in flagellation. Previous work determined that F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 52 publications
5
95
1
1
Order By: Relevance
“…The amphiphilic nature of this molecule hinders it from freely crossing the membrane into the cellular interior except through the endocytic pathway, as extensively characterized in eukaryotic cells (30,31). FM 4-64 has also been widely used in bacterial cells and shown to specifically label membranes but not extracellular protein filaments such as flagella (32,33), except in a few bacterial species where flagella are coated in membrane sheaths (34). To our surprise, the entire length of the Shewanella nanowires was clearly stained with this reliable lipid bilayer dye (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The amphiphilic nature of this molecule hinders it from freely crossing the membrane into the cellular interior except through the endocytic pathway, as extensively characterized in eukaryotic cells (30,31). FM 4-64 has also been widely used in bacterial cells and shown to specifically label membranes but not extracellular protein filaments such as flagella (32,33), except in a few bacterial species where flagella are coated in membrane sheaths (34). To our surprise, the entire length of the Shewanella nanowires was clearly stained with this reliable lipid bilayer dye (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The H. pylori genome encodes four flagellar switch proteins (FliG, FliM, FliN, and FliY) (15) compared to the three switch proteins (FliG, FliM, and FliN) in Salmonella and E. coli. It has been shown that each of the four switch proteins is required for wild-type levels of flagellation and function.…”
mentioning
confidence: 99%
“…Chen et al (2011) demonstrated by some cryo-EM studies that the main core of C-ring in most of the bacteria is principally regulated by the presence of FliG, FliM and FliN, but not FliY. According to Lowenthal et al (2009), FliY protein has an N-termianl domain that belongs to CheC/CheX/FliY/FliM family. Due to its feature, it is possible that FliY may substitute FliM in FliG Cdomain interaction, but experimental confirmation is lacking.…”
Section: Model Amentioning
confidence: 99%
“…Moreover, FliN is involved in the direct binding of the regulator protein CheY-P (Paul and Blair, 2006). Lowenthal et al (2009) performed some alignment of FliN and FliY sequences taken from well characterized bacteria. They noticed highly conserved structural regions, even though some specific amino acids were not.…”
Section: Model Amentioning
confidence: 99%